Adaptive Gamification and AI-Powered Feedback in Primary English Education: A Personalized Learning Approach - Murphy, Adrian Paul Duffy (International Journal of Scientific Research and Management (IJSRM), 2025)
The integration of adaptive gamification and artificial intelligence (AI)-powered feedback represents a transformative shift in primary English education, offering pathways toward highly personalized learning experiences. This paper examines how combining game-based learning strategies with AI-driven feedback mechanisms can enhance cognitive, emotional, and motivational outcomes for young learners of English as a Foreign Language (EFL).The findings highlight that adaptive gamification—through dynamic learning pathways, interactive tasks, and reward systems—can significantly improve vocabulary retention, learner engagement, and motivation. When coupled with AI-powered feedback, students receive real-time formative assessments, individualized guidance, and tailored interventions that surpass traditional teaching methods. These adaptive systems are shown to accommodate differences in learning styles, readiness, and pacing, making them highly suitable for diverse primary school classrooms.To support the analysis, tables and graphical representations illustrate comparative outcomes between gamified and non-gamified approaches, as well as longitudinal trends in the application of AI and gamification in education. Key challenges, including ethical considerations, over-gamification risks, and infrastructural limitations, are also discussed.Overall, the research emphasizes the pedagogical potential of blending adaptive gamification with AI-driven feedback as a framework for personalized learning in primary English education. This hybrid approach not only enhances academic achievement but also fosters sustained motivation, learner autonomy, and inclusive classroom practices. Future directions call for longitudinal and cross-cultural studies to validate outcomes, alongside policy-driven strategies to ensure ethical and equitable integration of AI in early education.Keywords: Adaptive gamification, AI-powered feedback, personalized learning, primary English education, EFL, intelligent tutoring systems.